2013
DOI: 10.1021/ja4021638
|View full text |Cite
|
Sign up to set email alerts
|

Size Specifically High Activity of Ru Nanoparticles for Hydrogen Oxidation Reaction in Alkaline Electrolyte

Abstract: The hydrogen oxidation reaction (HOR) in alkaline electrolyte was conducted on carbon-supported Ru nanoparticles (Ru/C) of which size was controlled in the range from approximately 2 to 7 nm. The HOR activity of Ru/C normalized by the metal surface area showed volcano shaped dependence on the particle size with a maximum activity at approximately 3 nm. The HOR activity of approximately 3 nm Ru/C was higher than commercially available Pt nanoparticles (ca. 2 nm) supported on carbon. The structural analysis of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
180
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(195 citation statements)
references
References 38 publications
14
180
1
Order By: Relevance
“…Inspired by this work, some recent studies have further explored the kinetics of the HOR on Ir 23 and Ru, 23,24 which are typically more affordable than Pt 25 but also 1-2 orders of magnitude less abundant. 26 Alternatively, palladium mining resources are comparable to those for platinum, 26 while typically remaining 2-3 fold less expensive than Pt.…”
Section: −2mentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by this work, some recent studies have further explored the kinetics of the HOR on Ir 23 and Ru, 23,24 which are typically more affordable than Pt 25 but also 1-2 orders of magnitude less abundant. 26 Alternatively, palladium mining resources are comparable to those for platinum, 26 while typically remaining 2-3 fold less expensive than Pt.…”
Section: −2mentioning
confidence: 99%
“…[17][18][19] Indeed, the implementation of this pH effect on the modeling of the electrochemical interface is only in its initial stage, 20,21 but should prove crucial for unveiling the fundamental reasons for these differing behaviors in a near future. In the meantime, Strmcnik et al have recently demonstrated a remarkable improvement of the HOR-kinetics on Pt in 0.1 M KOH following the addition of an oxophilic metal component, 22 either as an alloy (e.g., Pt 0.1 Ru 0.9 ) or through decoration of the Pt-surface with Ni(OH) 2 -adislands.Inspired by this work, some recent studies have further explored the kinetics of the HOR on Ir 23 and Ru, 23,24 which are typically more affordable than Pt 25 but also 1-2 orders of magnitude less abundant. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Sun et al reported increased activity with increased particle size for HOR/HER on 2-7 nm Pt nanoparticles in acid, 18 and Ohyama et al reported the same trend for HOR/HER on 2-4 nm Pt nanoparticles in base. 19 However, the rotating disk electrode (RDE) method cannot be used to measure HOR/HER activity on Pt in acid due to the overlapping polarization and concentration overpotential curves, 8,20 and thus the results from Sun et al 18 via RDE measurements might not be reliable. Using the H 2 -pump method in a proton exchange membrane fuel cell configuration, Durst et al characterized the exchange current densities of HOR/HER on 2-9 nm Pt/C and reported no particle size effect.…”
mentioning
confidence: 99%
“…Ohyama et al explored the particle size effect of HOR/HER on Ru nanoparticles in 0.1 M NaOH, and their results indicated an optimum exchange current density at particle size of 3 nm due to the optimum ratio of amorphous-like Ru on the surface at 3 nm. 19 Zheng et al reported that the specific HOR/HER exchange current density on Ir/C in 0.1 M KOH increases as particle size increases from 3 to 12 nm. 22 In this study, we investigate the particle size effect for HOR/HER via RDE measurements in both acidic and alkaline electrolytes on Pd/C catalysts with the Pd particle size ranging from 3 to 42 nm.…”
mentioning
confidence: 99%